A new role for an ancient variable in Appalachia: Paradigm leveling and standardization in West Virginia. (29th April 2014) - Hazen, Kirk
Abstract In many rural English-speaking communities, linguistic processes such as paradigm leveling come into direct conflict with social processes of standardization. In the US region of Appalachia, an analysis of past be leveling illustrates the progression of the sociolinguistic clashes between these forces. A quantitative sociolinguistic examination of leveled was (e.g., We was there) for 67 native Appalachian speakers was conducted to assess the status of past be in light of economic and educational improvements over the 20th century. The results indicate that leveled was declined sharply, with the youngest speakers demonstrating more standardized patterns. Although the overall rate of was leveling declined across apparent time, the rate of was contraction (e.g., We's there last night) increased, offering native Appalachians a reduced variant to contest the social push toward a fully standardized system.